Spelmansglädje - Sjölund, Jarl; Johansson, Chrisse, 1948-; Ramström, Hans-Erik; Sjölund, Jarl (Kumlinge : Jarl Sjölund, 2012)
16 kappaletta.
Jarl "Jalle" Sjölund (harmonikat, lauluääni), Christina Johansson (viulut, bassokitara), Hans-Erik "Hanski" Ramström (kitara).
Sanat tekstiliitteessä (kappaleet 9-11): ruotsi.
Keywords: kansanmusiikki; pelimannimusiikki